2010
DOI: 10.1021/ja909716k
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Intermolecular Aminofluorination of Styrenes

Abstract: A novel palladium-catalyzed intermolecular aminofluorination of styrenes, with N-fluorobenzenesulfonimide (NFSI) functioning not only as a fluorinating reagent but also as an aminating reagent, has been developed. The reaction afforded vicinal fluoroamine products with very high regioselectivity. This transformation may involve fluoropalladation of styrene as a key step for C-F bond formation. The bidental nitrogen ligand is crucial to achieving the transformation successfully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0
7

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 276 publications
(102 citation statements)
references
References 22 publications
2
93
0
7
Order By: Relevance
“…The ligand screening results showed that bathocuproine is better than the others (entries 6, 11e12). It is worthy noted that the aminofluorination product was obtained in the absence of alcohol [16].…”
Section: Resultsmentioning
confidence: 97%
“…The ligand screening results showed that bathocuproine is better than the others (entries 6, 11e12). It is worthy noted that the aminofluorination product was obtained in the absence of alcohol [16].…”
Section: Resultsmentioning
confidence: 97%
“…An application of palladium-catalyzed electrophilic fluorination was reported by Liu and coworkers in 2010 [50]. Imidofluorination of styrenes with NFBS occurred regioselectively (Fig.…”
Section: Reactions Proposed To Proceed Via Two-electron Pathwaysmentioning
confidence: 94%
“…25 (1) Liu and co-workers disclosed a regioselective Pd-catalyzed intermolecular aminofluorination of styrenes in 2010 using NFSI as the fluorine source and stoichiometric (2.5 equiv) oxidant (Scheme 21). 26 The regioselectivity is analogous to a Markovnikov electrophile-initiated haloamination. The authors proposed a mechanism involving fluoropalladation and subsequent C-N bond formation from the organopalladium intermediate.…”
Section: Intermolecular Catalyticmentioning
confidence: 99%